Deciphering Density Fluctuations in the Hydration Water of Brownian Nanoparticles via Upconversion Thermometry - Maturi, Fernando E. [UNESP]; Raposo Filho, Ramon S.; Brites, Carlos D. S.; Fan, Jingyue; He, Ruihua; Zhuang, Bilin; Liu, Xiaogang; Carlos, Luís D. (American Chemical Society (ACS), 2024)
We investigate the intricate relationship among temperature, pH, and Brownian velocity in a range of differently sized upconversion nanoparticles (UCNPs) dispersed in water. These UCNPs, acting as nanorulers, offer insights into assessing the relative proportion of high-density and low-density liquid in the surrounding hydration water. The study reveals a size-dependent reduction in the onset temperature of liquid-water fluctuations, indicating an augmented presence of high-density liquid domains at the nanoparticle surfaces. The observed upper-temperature threshold is consistent with a hypothetical phase diagram of water, validating the two-state model. Moreover, an increase in pH disrupts the organization of water molecules, similar to external pressure effects, allowing simulation of the effects of temperature and pressure on hydrogen bonding networks. The findings underscore the significance of the surface of suspended nanoparticles for understanding high- to low-density liquid fluctuations and water behavior at charged interfaces.